Faktor Risiko Keluhan Musculoskeletal Disorders Pada Penjahit Di Pasar Tradisional Kabanjahe - Cleo Dora Aurelia Br. Ginting; Mutiara Nandika; Putranto Manalu; Santy Deasy Siregar (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Musculoskeletal Disorders (MSDs) are a major occupational health issue among informal-sector tailors due to prolonged static postures and repetitive movements. This study aims to analyze risk factors associated with MSDs complaints among tailors at Kabanjahe Traditional Market. A quantitative cross-sectional design was applied with total sampling of 63 tailors, using the Nordic Body Map (NBM) questionnaire, Rapid Entire Body Assessment (REBA) worksheet, and a lux meter. Data were analyzed with the Chi-Square test (α = 0.05). The results showed that 63.5% of tailors experienced MSDs. Significant associations were found between MSDs and age (p = 0.020; OR = 4.359), years of service (p = 0.040; OR = 3.667), working duration (p = 0.005; OR = 6.417), and working posture (p = 0.005; OR = 6.417). Sex, lighting, and BMI showed no significant association (p > 0.05). Working duration and posture were the most dominant risk factors. Tailors are advised to improve posture, use supportive chairs, and perform regular stretching to prevent MSDs.